Cognitive and social skills in collaborative solution of mathematical problems - Chandia, Eugenio (2022)
[Objective] The objective of this study was to analyze the cognitive and social skills of a group of students and their teacher in an exercise based on Collaborative Problem Solving (CPR) in Mathematics. [Methodology] A study was carried out by selecting one of the 8 groups of 4 students randomly assigned in a non-curricular exercise scheduled in 24 biweekly sessions of 90 minutes. The group selected consisted of 4 female students. The sessions were recorded, and data on the interactions between subjects (students and teacher) were coded at the beginning and at the end of the exercise for factors including skills of representation, regulation, communication and roles assumed in group work, and interaction with the teacher. The coded data were subsequently analyzed using asymmetric graph analysis techniques to measure the intensity of interactions, and correspondence analysis to determine the significance of relationships between the sub-skills involved. Rstudio software was used to carry out the analysis. [Results] A significant change in the intensity of interactions between participants was observed throughout the implementation with respect to the centrality and closeness indices associated with the graphs obtained. [Conclusions] The systematic CPR work in mathematics carried out in the exercise promotes and modifies social and cognitive skills and their interaction.